Effectiveness of Rehabilitation Program for Chronic Schizophrenia: A Case Study - Sarwar, Anila; Bashir, Umaiza (Journal of Liaquat University of Medical & Health Sciences, 2019)
Chronic schizophrenia is a longer term state of schizophrenia and it is marked by persistent patterns of distorted perception of reality, thought processes and negative as well positive symptoms. It disrupts the executive functioning of the individual that’s why all areas of a person’s life turned effected because of this. As an old practice to treat this psychotic disorder only medicines were used but presented case highlighted the importance of psychotherapy (rehabilitation) along with medication for the better management of chronic schizophrenia. It highlighted the significance of Rehabilitation process for regaining the elapsed simpler and smaller but essential life skills for managing schizophrenia. The cultural reservations were there while assessing and managing this case.